Analysis of donor deferral at three blood centers in Brazil. Issue 3 (31st July 2012) - Gonçalez, Thelma T.; Sabino, Ester C.; Schlumpf, Karen S.; Wright, David J.; Mendrone, Alfredo; Lopes, Maria; Leão, Silvana; Miranda, Carolina; Capuani, Ligia; Carneiro‐Proietti, Anna Barbara F.; Basques, Fernando; Ferreira, João E.; et al.
<x xml:space="preserve">Abstract</x> BACKGROUND: The safety of the blood supply is ensured through several procedures from donor selection to testing of donated units. Examination of the donor deferrals at different centers provides insights into the role that deferrals play in transfusion safety. STUDY DESIGN AND METHODS: A cross‐sectional descriptive study of prospective allogeneic blood donors at three large blood centers located in São Paulo, Belo Horizonte, and Recife, Brazil, from August 2007 to December 2009 was conducted. Deferrals were grouped into similar categories across the centers, and within each center frequencies out of all presentations were determined. RESULTS: Of 963, 519 prospective blood donors at the three centers, 746, 653 (77.5%) were accepted and 216, 866 (22.5%) were deferred. Belo Horizonte had the highest overall deferral proportion of 27%, followed by Recife (23%) and São Paulo (19%). Females were more likely to be deferred than males (30% vs. 18%, respectively). The three most common deferral reasons were low hematocrit or hemoglobin, medical diagnoses, and higher‐risk behavior. CONCLUSION: The types and frequencies of deferral vary substantially among the three blood centers. Factors that may explain the differences include demographic characteristics, the order in which health history and vital signs are taken, the staff training, and the way deferrals are coded by the centers among other policies. The results indicate that blood donor deferral in Brazil has regional aspects that should be considered when national policies are developed.